A strategically oriented conception of optical prevention of myopia onset and progression - E. P. Tarutta; O. V. Proskurina; G. A. Markossian; S. V. Milash; N. A. Tarasova; N. V. Khodzhabekyan (Российский офтальмологический журнал, 2020)
The article presents a theoretical and clinical justification for optical techniques used for the prevention of myopia. Accommodation, wavefront aberrations, peripheral refraction, and retinal image quality are considered as interrelated factors affecting postnatal refractogenesis. A detailed analysis of myopia correction methods, conditions preceding its development and their impact on the dynamics of refraction and eye growth is given. A strategy of optical correction of myopia was proposed, which includes: 1) constant wearing of defocusing binocular positive spectacle lens or Perifocal-P spectacle lens (in case of exophoria) for children at risk aged 4–7 years; 2) constant alternating weak myopic defocusing in case of myopia from 0.5 to 2.75 D, ortho- or esophoria, positive relative accommodation (PRA), peripheral myopia or emmetropia; progressive addition spectacle lens in case of PRA less than 1.0 D; Perifocal-Msa spectacle lens in the case of a combination of reduced PRA and exophoria; 3) Perifocal-M spectacle lens in case of myopia of any degree with already existing hyperopic peripheral defocus; progressive addition spectacle lens in case of PRA less than 1.0 D in combination with esophoria or Perifocal-Msa spectacle lens in combination with exophoria; 4) contact correction with bifocal soft contact lenses or orthokeratological contact lenses (Ortho-K) in case of refusal from spectacle correction. Ortho-K is preferable with moderate and high myopia; 5) bioptic correction: a combination of monofocal soft contact lenses and Perifocal-M spectacle lens to correct peripheral defocus and residual astigmatism is preferable for myopia over 8.0 D and myopia with astigmatism.